Estimate Suitable Location of Solar Power Plants Distribution by GIS Spatial Analysis - Baydaa Abdul Hussein Bedewy; Sophia Rezaq Ali Al-Timimy (Salehan Institute of Higher Education, 2023)
This study proposes a model for the best investment in renewable energy plants that uses DEM, Spatial Analysis, and analysis of indicator weights by AHP to choose a suitable place to locate the solar plants, which increases their efficiency. This is because renewable energy is the most important component of future sustainability. In addition, the cities of Iraq, including Babylon, have increased the proportion of the population, which has led to high rates of urbanization and a lack of services. In particular, the need for services increased, especially electric power, which is characterized by its inefficiency and insufficiency. Yet, the governorate is a good source of solar energy and regular radiation. Therefore, the trend to use renewable energy is the optimal solution, and this manuscript proposes multiple criteria that can determine the optimal locations for building solar energy farms. So methods of analysis are the Digital Elevation Model (DEM), the slope of the earth, efficient distances from the city center, the main road networks and electricity distribution networks, and average solar brightness (hours/day) quantity. Finally, the spatial analysis of all indicators shows eight sites. By using criteria of analysis based on AHP analysis, the result is that six represent suitable sites chosen as sufficient space to locate solar plants. Consequently, the results of this manuscript for solar energy collection projects show percentages ranging between 2% and 37%, with areas starting with 10 ‎km2 and gradually rising towards the largest proposed area of 155 km2, distributed over the province so that the total proposed areas for solar energy collection projects will be about 422 km2. All that aim to achieve the best service in quality and quantity of renewable energy to establish sustainability and efficiency economic modeling in addition to increasing production efficiency. Doi: 10.28991/CEJ-2023-09-05-013 Full Text: PDF